Answer:
(x, y) = (-2, 2)
Step-by-step explanation:
We are given the following two equations which we are to solve using the substitution method:
[tex]x - y = -4[/tex] --- (1)
[tex]x - 2y = -6[/tex] --- (2)
From equation (1):
[tex]x = y-4[/tex]
Substituting this value of x in (2) to get:
[tex]x = [tex]x - 2y = -6\\\\(y-4)-2y=-6\\\\-y=-6+4\\\\-y=-2[/tex][/tex]
y = 2
Substituting the value of y in (1) to get x:
[tex]x - y = -4[/tex]
[tex]x - 2 = -4[/tex]
[tex]x = -4 + 2[/tex]
x = -2
Therefore, (x, y) = (-2, 2).